Teenagers Delinquency Motivation and Prevention: – Take the case of Wu Xieyu’s matricide case - Tao, Yuhan (Transactions on Social Science, Education and Humanities Research, 2023)
This paper summarizes the characteristics of teenager delinquency by reading literature and analyzes the characteristics of Wu Xieyu’s matricide case. Finally, measures to reduce teenagers delinquency are proposed from the perspectives of improving family relationships, managing the network environment, and providing psychological treatment.